A recommendation for a budget management information system - Ong, Andrew Jayson T. (University of the Philippines Diliman, 2004)
The proposal for Budget Management Information System has its roots in another project called the Budget Management System, which is geared towards the implementation of budgeting as a means of performance evaluation and generation of cost saving opportunities. It was brought about due to the lack of an enabling environment wherein such a system would be able to become part of the regular operations of the various Accounting Departments in the company. The situation requires an integrated approach to the requirements. With the soft side being part of the ongoing project, the hard part or the technology solution will be met by this new project (BMIS). This aspect is a new initiative as it was assumed that the current Accounting practices could support the BMS but actual results have born out the opposite. The proposal that would be generated by this project will be forwarded to the Executive Vice President where high level discussions between him and the proponent is expected to result in adoption of at least part of the proposal. Expected beneficiaries include the Accounting Department, Top Management and the Middle Management. This project provides a unique opportunity to introduce the company to the concepts used in technology management especially when it comes to the task of technology acquisition. Such projects were often postponed, just done as after thought or proposed by the consultants hired by the company. This approach provides a sustainable way of generating such initiatives internal to the company.